Genere, disabilità, linguaggio Progetti e prospettive a Milano - Brambilla, Marina (I diritti negati, 2021)
The book illustrates and analyzes separately the relationships between language and gender and language and disability. By interlacing legal and linguistic approaches, the book aims at unraveling challenges and criticisms surrounding the use of the language which are likely to impair and violate the constitutional and supranational principle of equality and non-discrimination. Despite the variety of implications and the specifics of each language, the book chooses to hinge more broadly on the Italian and German languages, unified by being both examples of "gendered languages".